The influence of the shape of the end faces on the efficiency of a cycloidal rotor - Dekterev Dmitrii; Dekterev Aleksandr; Dekterev Artem; Neobyavlyayushchiy Pavel (E3S Web of Conferences)
The paper presents the results of an experimental and numerical study of the aerodynamic and thrust-energy parameters of a cycloidal rotor depending on the geometric features of the end faces. It has been shown experimentally and by numerical methods that the use of end disks with sharp edges leads to the formation of a separated flow and a decrease in the effective surface area of the wing. Various design options for end fairings are considered. The expediency of using inward-rounded fairings forming a uniform input flow to the entire plane of the rotor blades is shown. The use of fairings leads to an increase in aerodynamic efficiency of up to 8%. Changing the rotor design by placing blade control mechanisms inside a profiled end faces leads to an increase in efficiency of more than 12%.